Visual Evoked Potentials to Monitor Myelin Cuprizone-Induced Functional Changes - Marenna, Silvia; Huang, Su-Chun; Dalla Costa, Gloria; d’Isa, Raffaele; Castoldi, Valerio; Rossi, Elena; Comi, Giancarlo; Leocani, Letizia (Frontiers in Neuroscience, 2022)
The visual system is one of the most accessible routes to study the central nervous system under pathological conditions, such as in Multiple Sclerosis (MS). Non-invasive Visual Evoked Potential (VEP) and Optical Coherence Tomography (OCT) were used to assess visual function and neuroretinal thickness in C57BL/6 taking 0.2% cuprizone for seven weeks and at 5, 8, 12, and 15 days after return to normal diet. VEPs were significantly delayed starting from 4 weeks on cuprizone, with progressive recovery off cuprizone, becoming significant at day 8, complete at day 15. In contrast, OCT and neurofilament staining showed no significant axonal thinning. Optic nerve histology indicated that whilst there was significant myelin loss at 7 weeks on cuprizone diet compared with healthy mice, at 15 days off cuprizone diet demyelination was significantly less severe. Number of Iba 1+ cells, was found increased in cuprizone mice at 7 weeks on and 15 days off cuprizone. The combined use of VEPs and OCT, allowed us to characterize non-invasively, in vivo, the functional and structural changes associated with demyelination and remyelination in a preclinical model of MS. This approach offers a contribution to the non-invasive study of possible effective treatments to promote remyelination in demyelinating pathologies